INFLUENCE OF NUTRITIOUS DIETS ON COMPENSATORY GROWTH AND MEAT PRODUCTIVITY OF STEERS - K.I., Khidirov (Eurasian Journal of Academic Research, 2022)
The ways of intensive rearing influence on the meat productivity of the stunted young cattle of Simmental breed and the ways of rational using of genetic possibilities of the animals of the studied groups for increasing the production of high-quality beef and increasing the profitability of the branch have been revealed. The experimental data replenish the scientific information and substantiate the comprehensive research on improving the Simmental breed and give practical recommendations for organizing the rearing of young animals, taking into account the weight and age specificity. The determined biological laws of growth and development of the tissues supplement and expand the views on the quantitative and qualitative estimation of the meat productivity of young animals.